Pengaruh Independensi dan Gaya Kepemimpinan Pada Skeptisisme Profesional Auditor - Pratami, Dhaniar Waghmi; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
Auditors who apply professional skepticism will be critical in conducting audit assignments taking into account existing risks and collecting audit evidence. In order for skepticism to be achieved, auditors need to pay attention to factors that can influence the skepticism of professional auditors. The purpose of this study was to determine the effect of independence and leadership style on professional skepticism of auditors. This research was conducted at the Denpasar Regional Public Accountant Office (KAP). The number of samples obtained based on the purposive sampling method is 45 people. Data collection using the questionnaire method. Based on the results of the analysis it was found that independence and leadership style had a positive influence on the auditor's professional skepticism. Keywords : Independence, leadership, professional audit skepticism.